1997
DOI: 10.1577/1548-8659(1997)126<1012:sfivhe>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Fishes in Vegetated Habitats: Effects of Habitat Structure on Sampling Characteristics of the 1-m2Throw Trap

Abstract: Enclosure traps that quickly surround well-defined areas of habitat are perhaps the most widely used method for sampling fishes in vegetated habitats. However, relatively few data are available to evaluate the effects of habitat structure on sampling characteristics of enclosure traps. In this study, we determined how clearing efficiency and accuracy of 1-m 2 throw traps varied across a range of environmental conditions in the Florida Everglades by sampling within enclosed areas of marsh habitat. Throw trap cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 32 publications
1
71
1
Order By: Relevance
“…Our findings that seagrasses support greater overall abundance, richness, and diversity relative to unve- getated substrate are consistent with earlier reports that structurally complex habitats support more individuals and species (Lewis, 1984;Jordan et al, 1997a). The basket shell, pinfish, and rainwater killifish (Lucania parva), for example, displayed dramatic preferences for seagrass over unvegetated substrate, and this contributed to these differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings that seagrasses support greater overall abundance, richness, and diversity relative to unve- getated substrate are consistent with earlier reports that structurally complex habitats support more individuals and species (Lewis, 1984;Jordan et al, 1997a). The basket shell, pinfish, and rainwater killifish (Lucania parva), for example, displayed dramatic preferences for seagrass over unvegetated substrate, and this contributed to these differences.…”
Section: Discussionsupporting
confidence: 91%
“…Comparisons of epifauna found in seagrass meadows and adjacent bare substrates have shown that diversity and abundance is higher (Thayer et al, 1975;Orth, 1977;Virnstein et al, 1983;Bell et al, 1984;Lewis, 1984;Orth et al, 1984;Sogard, 1992;Jordan et al, 1997a;Arrivillaga and Baltz, 1999) and predation lower (Virnstein et al, 1983;Summerson and Peterson, 1984) in vegetated habitats. Arrivillaga and Baltz ( 1999), for example, found that crustacean and fish abundances were 7 and 20 times higher, respectively, in meadows of turtle grass ( Thalassia testudinmn) than over sand.…”
mentioning
confidence: 99%
“…Fish were collected using two methods: throw trap -(consisting of a cubic metal structure (1m³) with the four sides covered by a nylon 1.5 mm mesh) -that is efficient for the collection of individuals up to 100 mm in length (Jordan et al, 1997;Baber et al, 2002, Pelicice et al, 2005, and gill netefficient for different size classes. These fishing techniques were used on different days, so that one method did not interfere with the efficiency of the other.…”
Section: Samplingmentioning
confidence: 99%
“…These temporary water bodies are formed by the expansion of the littoral zone of the permanent water bodies during each new flood cycle (Junk et al, 1989;Ward et al, 2002). The high availability of nutrients in the system during flooding stimulates the rapid growth of microorganisms, invertebrates and aquatic macrophytes, providing food and shelter for species that exploit this environment (Jordan, et al, 1997;Lowe-McConnell, 1999;Penha et al, 1999;Saint-Paul et al, 2000;Agostinho et al, 2001;Li & Gelwick, 2005). The magnitude and duration of the flood may act in a different way on species that use temporary habitats to complete their life cycle, thus affecting the species composition of aquatic communities that use the river-plain system Petry et al, 2003;Thomaz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, I was particularly interested in the ability of these fish to survive rapid shifts in salinity because freshwater is presently being diverted via canals, and this will directly affect salinities in the northeastern Florida Bay. It is unlikely that the overall (chronic) level of salinity affects distribution of these fish because they occur over a wide range of salinities (Table 1) Fish were collected with a 1-m 2 throw trap (Kushlan, 1981), which is the most effective gear available for sampling demersal organisms on the shallow, soft mud banks of Florida Bay (Powell et al, 1986;Jordan et al, 1997 Three replicates were completed for each treatment; therefore, a total of 108 individuals were tested for each species (nine treatments X four fish per aquaria X three replicates). Filtered seawater (30 ppt) was diluted with deionized water for salinities of 5-30 ppt.…”
Section: Salinity Tolerance Of Two Goblesmentioning
confidence: 99%